Pengembangan Self Help Book untuk Mengatasi Kesepian pada Remaja dengan Teknik Menulis Cerita - Rina Fitriana; Karsih; Fitri, Susi (INSIGHT: Jurnal Bimbingan Konseling, 2022)
This study aims to produce an instructional book about to overcome loneliness by story writing aimed at class VIII in junior high schools in Tangerang. The research method used is the Design By Research (DBR) method which consists of four stages of the model, analysis-exploration, design-construction, analysis-reflection, implementation. Formative evaluation had be done by a validation evaluation 88% (very feasible), validity of the material experts is 78% (adequate), validity of guidance counseling teacher is 100% (very feasible) and the students are 90% (very feasible). The result of the research is a book that contains the stages of story writing using story theory from the perspective of narrative therapy.